EVALUASI PENERIMAAN CALON PEGAWAI NEGERI SIPIL DAERAH (CPNSD) PEMERINTAH PROPINSI JAWA TENGAH TAHUN 2013 - Herawati, Nunik Retno (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Central Java Provincial Government in 2013 organized a Candidate Registration Regional Civil Servants (CPNSD) on line system. Selection is done by stages: Selection Administration and Basic Competence Test (TKD) through Computer Assisted Test (CAT) with the facilitation of the State Personnel Board (BKN) .The researchers have assumed that the acceptance CPNSD in Regional Government of Central Java Province in 2013 is better than the previous year. In general, the implementation CPNSD 2013 in Central Java Province has been implemented and run better when compared with the previous year CPNSD implementation. Indications are good transparency in the registration stage to the stage of graduation announcements. At the registration stage, the transparency shown by the use of the Internet media that can be accessed by all people. In the explanation, the public can see clearly the requirements and application procedures CPNSD. However, in the online registration is still frequently encountered obstacles such as the presence slowness internet access by prospective applicants CPNSD in Central Java. Acceptance CPNSD in Central Java in 2013 that uses CAT system has many advantages and can minimize cheating because its value can be directly known to be more objective, in addition to the basic competence test execution process faster, practical and efficient which will save costs.